Early weaning-related pathologies: How to prevent? (Research, Society and Development, 2021)
Objective: To characterize the possible pathologies associated to the early weaning with the contribution of a poor dietary introduction in the last 10 years. Methodology: This is a bibliographic review, the search for the material was carried out online in large databases, such as Lilacs, Pubmed and Capes. For sample selection, the inclusion criteria were used: online articles, available in full, full article, master's / doctoral thesis, free articles, published in Portuguese and Spanish, in the period between 2010 and 2020 and that included the chosen subject to be studied. Result: The selected publications corroborate the innumerable benefits of breastfeeding in preventing diseases, in the different stages of infant life, report on the factors that contribute to early weaning and poor dietary introduction. Final considerations: Among the studies, most employ that the early introduction of food is associated with the risk of children being overweight and obese. Throughout the study, there were several limitations in the search for articles on the subject, so it is necessary to have more studies and research related to this discussion.